Pengaruh Emotional Demand, Emotional Exhaustion, dan Abusive Supervision terhadap Turnover Intention - Nabila Eka Putri; Tiarapuspa Tiarapuspa (Widya Manajemen, 2023)
The purpose of this study is to analyze the influence of emotional demand, emotional exhaustion, and abusive supervision on turnover intention. In this study, primary data was collected using a questionnaire on a google form filled out by Trisakti University students who were already working. The data collection method uses the purposive sampling method with a sample of 165 samples. The data processing techniques used in this study were testing instruments such as validity and reliability tests and Structural Equation Modeling (SEM) using SPSS version 25 and AMOS version 24. The results of this study revealed that emotional demand has a significant influence on turnover intention, emotional exhaustion has a significant influence on turnover intention, and abusive supervision has a significant influence on turnover intention.